2019
DOI: 10.14744/alrj.2019.50479
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Iranian High School Students’ Use of Request Speech Act

Abstract: The recent advances in technology and increased opportunity for second language (L2) learners to communicate with native speakers make learning pragmatic competence and principles of appropriate language use indispensable to successful language acquisition. In view of the aforesaid fact, the present study set out to explore the most frequent strategy used by Iranian English as a foreign language (EFL) learners regarding the speech act of request and examine the effectiveness of the Iranian mainstream high scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Hence, it can be concluded that, in this study, Iranians as foreign language learners of English were sociopragmatically aware of the norm of the target language regarding the level of directness in requests. Previous studies conducted on Iranian EFL learners also confirm participants’ pragmatic competence in choosing the level of directness (Hashemian, 2014; Hashemian & Farhang-Ju, 2017; Jalilifar, 2009; Panahzadeh & Asadi, 2019); this is particularly of importance because Iranians as native speakers of Persian use direct strategies the most (Hashemian, 2014; Kalantari Khandani, 2017), while at the same time accompanying direct requests with several internal and external modifiers (Kalantari Khandani, 2017). Contrary to this study, however, Bu (2012) and Jalilifar (2009) reported pragmatic development with the increase in proficiency; the use of conventionally indirect requests grew with proficiency.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Hence, it can be concluded that, in this study, Iranians as foreign language learners of English were sociopragmatically aware of the norm of the target language regarding the level of directness in requests. Previous studies conducted on Iranian EFL learners also confirm participants’ pragmatic competence in choosing the level of directness (Hashemian, 2014; Hashemian & Farhang-Ju, 2017; Jalilifar, 2009; Panahzadeh & Asadi, 2019); this is particularly of importance because Iranians as native speakers of Persian use direct strategies the most (Hashemian, 2014; Kalantari Khandani, 2017), while at the same time accompanying direct requests with several internal and external modifiers (Kalantari Khandani, 2017). Contrary to this study, however, Bu (2012) and Jalilifar (2009) reported pragmatic development with the increase in proficiency; the use of conventionally indirect requests grew with proficiency.…”
Section: Discussionmentioning
confidence: 65%
“…While studies conducted on request speech act extensively investigated request realization for directness and politeness (Esfahlan & Boroumand, 2020; Ghasempour & Farnia, 2016; Lenchuk & Ahmed, 2019; Panahzadeh & Asadi, 2019) and internal and external modifications (Abdolrezapour, 2015; Abdolrezapour & Eslami-Rasekh, 2012; Economidou-Kogetsidis, 2009; Göy et al, 2012), this study aims to also examine request perspective, which as stated by Ogiermann and Bella (2020) is the least studied mitigation form in request speech act studies and thus very few studies examined this aspect (e.g., Economidou-Kogetsidis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research recognizes that language usage can change based on the context, the relationship between speakers, and the setting of the communication (Demirkol, 2015), and students need to learn how to adapt their language to different situations, such as formal versus informal conversations or written versus spoken communication (Huwel & Ghayadh, 2020; Kecskes, 2015), this can be challenging as well. Some studies contend that language often contains ambiguity and indirectness, where the intended meaning is not explicitly stated, and teaching students to recognize and interpret these indirect cues, such as sarcasm, irony, or euphemisms, can be challenging (Panahzadeh & Asadi, 2019). Equally, pragmatic competence also involves understanding nonverbal cues like facial expressions, gestures, and body language, and teaching students to interpret and use these cues appropriately is crucial for effective communication, which may be demanding in many teaching settings (Zhang & Papi, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Incorporating pragmatic instruction into language curricula requires specialized teaching methods and materials that some teachers may not possess (Zhang & Papi, 2021). However, motivated students will be ready to learn, provided the instruction is tailored to their needs (Panahzadeh & Asadi, 2019). To overcome these challenges, educators may use different exercises, real-life scenarios, video examples, and cross-cultural discussions to motivate and provide students with practical experience using language effectively in various social contexts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation